First stage larva of the lobster shrimp Allaxius princeps (Boas, 1880) (Decapoda: Axiidea: Axiidae) obtained in the laboratory - Kornienko, Elena S.; Korn, Olga M. (Zootaxa, 2012)
First stage larva of the lobster shrimp Allaxius princeps (Boas, 1880) (Decapoda: Axiidea: Axiidae) obtained from theovigerous female is described and illustrated for the first time. It is the first description of the larva of lobster shrimp fromWest Pacific. Zoea I of A. princeps is characterized by the presence of four dorsal spines on the pleonal somites 2–5 andby the shape of the telson with a deep cleft but without a median process. Under these characters, zoea I of A. princeps is similar to the first larva of Axiopsis serratifrons.